Nonlinearity of Subtidal Estuarine Circulation in the Pearl River Estuary, China - Xu, Hongzhou; Shen, Jian; Wang, Dongxiao; Luo, Lin; Hong, Bo (Frontiers in Marine Science, 2021)
The Pearl River Estuary (PRE) is a bell-shaped estuary with a narrow deep channel and wide shoals. This unique topographic feature leads different dynamics of the subtidal estuarine circulation (SEC) in the PRE compared with a narrow and straight estuary. In this study, the nonlinear dynamics of the SEC in the PRE under mean circumstance are analyzed by using a validated 3-D numerical model. Model results show that the nonlinear advections reach leading order in the along-channel momentum balance. Modulated by tide, the nonlinear advections show significant temporal variations as they have much larger values during spring tide than that during neap tide. Unlike straight and narrow estuaries, both tidally and cross-sectionally averaged axial and lateral advections play important roles in driving the SEC in the PRE in which the axial advection dominates the nonlinear effect. But the two nonlinear terms balance each other largely resulting in a reduced nonlinear effect. Despite, the total nonlinear advection is still comparable with other terms and it acts as the baroclinic pressure to reinforce the SEC, especially during ebb tide, suggesting a flood-ebb asymmetry of the nonlinear dynamics in the PRE. In addition, diagnostic analyses of the along-channel vorticity budget show that nonlinear advections also make significant contribution to drive the lateral circulation in the PRE as Coriolis and baroclinic pressure terms, indicating complex dynamics of the circulation in the PRE.